Physics E-Book Design for High School Students Using Flip Pdf Professional Based on Edupark Hot Waterboom Solok Selatan - Titin Agustina; - Hamdi; Amali Putra; - Syafriani (PILLAR OF PHYSICS EDUCATION, 2020)
In facing the era of the industrial revolution 4.0, education is needed that can form a creative, innovative, and competitive generation. This can be achieved by optimizing the use of technology as a tool in education. In terms of education, the government made improvements to the learning system, namely curriculum development. The 2013 curriculum regulates learning resources, namely books, print and electronic media. But in reality the student books used in school only contain physics material and have not been fully integrated with the dimensions of attitude, spirituality, and local context. The existing teaching materials have not included the implementation of the 2013 curriculum and are not sufficient for students to learn independently. One solution to this problem is the physics e-book based on Edupark. This study aims to produce a physics e-book based on the Edupark Hot Waterboom in South Solok using a professional flip pdf for valid high school / MA students. The type of research used is development research using the Plomp development model. The plomp model is a research design suitable for developing research-based solutions in education. The plomp model is used to develop or validate theories about the learning process. The results of the validation test are used to test the advantages of the product that has been made and as a guide in making revisions to the e-book. The average value of each assessment component in the physics e-book based on the South Solok Water Boom Edupark can be determined from the average of the four assessment components including 1) content feasibility component 2) learning design component 3) display component and 4) software utilization component. From the percentage of the four components, the results of the e-book validation instrument were obtained by three validator experts with an average percentage of 85.11% with a very valid category